Overview of Risk Management Identification with the Root Cause Approach Analysis of the Cause of Safety Incidents in Hospital X - tanaya, evelyn marlia tanaya (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2026)
Patient safety is important to ensure safer patient care and prevent injuries due to mistakes, both due to actions taken and from not taking actions that should have been taken. One of the incidents that is a patient safety incident is a medical error. Medication errors at hospital X increased by 92.8% from 2023 to 2024, thus affecting the quality and safety of patients at Hospital X. The writing of this article was carried out to identify the root cause of the Patient Safety Incident to a follow-up plan that can be carried out at hospital X and to be an input for the Quality Improvement and Patient Safety Committee. The design of this article uses a cross sectional method using data from the 2024 patient safety incident report. Based on the data, the identification of the cause of the incident using the RCA method was carried out, which consisted of five steps, namely: problem identification, data collection, data analysis, root cause identification, and identification of corrective actions. In analyzing the data, root cause identification and improvement action identification were carried out with observation assisted by the RCA team that had been formed by RS X. Research From the incident report data, there were 54 incidents where the results of the data analysis obtained 11 green grading and 43 yellow grading so that the analysis was carried out using the CMP table and salted with fish bones for yellow grading. The results of root cause identification are from human resources factors such as many new personnel, not knowing the type of medicine, not used to using RME, lack of trained personnel, lack of anamnesia of officers. This can be prevented by planning training for officers. Medication errors at hospital X are caused by prescribing errors where hospital X can carry out the training process by using TNA to find out what training is needed. This research can be continued to find out whether implementing training can reduce the incidence of medical errors.